Sizing from the smallest scales: the mass of the Milky Way. Issue 4 (10th May 2022) - Rodriguez Wimberly, M K; Cooper, M C; Baxter, D C; Boylan-Kolchin, M; Bullock, J S; Fillingham, S P; Ji, A P; Sales, L V; Simon, J D
ABSTRACT: As the Milky Way and its satellite system become more entrenched in near field cosmology efforts, the need for an accurate mass estimate of the Milky Way's dark matter halo is increasingly critical. With the second and early third data releases of stellar proper motions from Gaia, several groups calculated full 6D phase-space information for the population of Milky Way satellite galaxies. Utilizing these data in comparison to subhalo properties drawn from the Phat ELVIS simulations, we constrain the Milky Way dark matter halo mass to be ∼1–1.2 × 10 12  M⊙ . We find that the kinematics of subhaloes drawn from more- or less-massive hosts (i.e. >1.2 × 10 12  M⊙ or <10 12  M⊙ ) are inconsistent, at the 3σ confidence level, with the observed velocities of the Milky Way satellites. The preferred host halo mass for the Milky Way is largely insensitive to the exclusion of systems associated with the Large Magellanic Cloud, changes in galaxy formation thresholds, and variations in observational completeness. As more Milky Way satellites are discovered, their velocities (radial, tangential, and total) plus Galactocentric distances will provide further insight into the mass of the Milky Way dark matter halo.